Numerical Experimentation for the Upgrade of Older-Design Eccentrically Braced Frame - Narayan; Pathak K.K. (My University, 2025)
This paper presents a retrofitting method for older-design eccentrically braced frame. Numerical experimentation was carried out for the old designed eccentrically braced frame and the modified versions of that the frame. Compared with a well-designed eccentrically braced frame designed using current seismic provisions, the behavior of the old designed eccentrically braced frame was not desirable. The contribution of the link in plastic dissipation was minimal even after following the criteria of shear link. Plastic dissipation by the frame, the braces, and the beam outside link was undesirably significant. The hysteresis loop was unstable, and significant strength degradation was observed. The structural behavior was improved by introducing the retrofitting measures in such a way that the structural interventions and the disruption to the occupants would be minimal. After modification, the maximum plastic dissipation was contributed by the link portion, as desired. The hysteretic behavior and the plastic dissipation were improved significantly, and the strength degradation was minimized. © 2021 American Society of Civil Engineers.